اﻟﺗﯾﺎرات اﻟﺳﯾﺎﺳﯾﺔ اﻟﺣزﺑﯾﺔ اﻟﻌراﻗﯾﺔ ﺑﻌد اﻻﺣﺗﻼل وﻣوﻗﻔﮭﺎ ﻣن إﻋﺎدة ﺑﻧﺎء اﻟدوﻟﺔ (Journal of the College of Education for Women, 2019)
This research focuses on Iraq. Parties and their role rebuilding The state of Iraq .the research starts with an introduction about the general concept of the state and a summary of the history of the iraqi state . then it surveys the most important Iraqi parties that are divided into three trends: the Islamic trend, the secular trend, and the Kurdish trend, that have different visions in reshaping and rebuilding the new Iraq: state. The research reaches to a result that the Iraqi state has started formation at least partially, after the announcement of 2005 constitution which includes: the new Iraq: from of political system that is based on democracy and federalism . in addition of other issues that out lines the new state of Iraq. Inspite that Iraqi parties come to in agreement in many major issues that are considered as the basic points for the program of the parties. If this difference has no consequences on in rebuilding Iraq , but it will leave its impact on the future as it is reflect on security and security deterioration, consequently lead to the deterioration of the general services and effecting rebuilding Iraq as a result.